Researching candidate sites for a carbon storage complex in the Central Appalachian Basin, USA. (September 2019) - Cumming, Lydia; Hawkins, Jared; Sminchak, Joel; Valluri, Manoj; Gupta, Neeraj
Highlights: Prefeasibility study for commercial-scale CCUS in the Appalachian Basin completed. Assessment included an analysis of sources and sinks, economics, and other factors. Project dimension and infrastructure requirements defined for two selected areas. Abstract: The purpose of the Central Appalachian Basin-Carbon Storage Assurance Facility Enterprise Integrated Prefeasibility Project was to identify candidate sites in eastern Ohio for a storage complex capable of storing 50 million tonnes. Carbon capture and storage (CCS) will be essential in the Appalachian Basin, which includes coal-fired power plants, natural gas processing, refineries, chemical plants, and natural gas power. The project team investigated Cambrian-Ordovician Age sandstones and carbonates collocated near depleted oilfields, where enhanced oil recovery could provide a stepping stone for developing a storage hub. Feasible routes for linking sources to sinks via regional pipelines were assessed. The sub-basinal analysis demonstrated significant potential storage capacity in both deep saline reservoirs and depleted oil and gas fields. The project definition analysis revealed the project footprint would be reasonable and only two wells would be needed for injection of CO2 . Project economics illustrated a need for both government and private investment in the absence of a regulatory mandate. Ohio also lacks a comprehensive policy for long-term liability and subsurface storage rights, which could be addressed during pilot testing. Developing qualified sites within two selected areas for large-scale deployment of CCS appears feasible and the study helped to define future research needs.